1410-P: Genetics of TG/HDL-C Ratio and Its Change over Time in Nondiabetic Subjects - AN, PING; LU, YANLI; THYAGARAJAN, BHARAT; KUIPERS, ALLISON L.; ANEMA, JASON A.; MILJKOVIC, IVA; DAW, EDWARD W.; PROVINCE, MICHAEL (Diabetes (New York, N.Y.), 2020)
TG/HDL-C ratio (THR) represents a single inherited surrogate predictor of hyperinsulinemia or insulin resistance that is associated with frank development of T2D, premature aging processes and increased mortality. To identify gene variants for THR and its change over time (THRGC), we conducted GWAS among subjects of European ancestry who had complete data from two exams collected ∼7 years apart from the LLFS (n = 3091), a study with familial clustering of exceptional longevity in the U.S. and Denmark. We sought replication in the FamHS (n = 3108, ∼7 years apart between two visits). Subjects with T2D or using medications for dyslipidemia were excluded from this analysis. THRGC was derived using growth curve modeling. Each phenotype was adjusted for age, sex, PCs and familial membership, and then log-transformed to approximate normality. EPACTS with make-kin and emmax options for familial clustering assuming additive genetic effects was used. P<5e-8 was used to declare genome-wide significance. Heritability estimates reached 38% for THR and 46% for THRGC in the LLFS. GWAS identified two significant loci for THR (LPL-rs328, stop gain, coding sequence variant, MAF=0.11, p=8e-9, replication p=4e-9; BUD13-ZNF259-APOA5-rs2072560, intron variant, MAF=0.07, p=2e-8, replication p=8e-14) and one locus for THRGC (LPL-rs78458743, ∼20 kb downstream, MAF=0.1, p=4e-8, replication p=0.01). The LPL gene encodes lipoprotein lipase that hydrolyzes chylomicrons and VLDL-C. Additionally, linkage scan identified a significant (Lods>3) locus on 3q28 (Lods=4.1) for THRGC in the LLFS. Further query of sequence elements under the linkage peak is underway. In conclusion, this first GWAS of THR identified the LPL gene (including a functional variant rs328) and the BUD13-ZNF259-APOA5 gene cluster for THR variation. The new findings highlight the importance of the LPL and APOA5 gene regulation of THR in subjects without diabetes selected for exceptional survival and healthy aging.